(untitled) - Schweizer, Peter (New York, 2004)
A portrait of the Bush family ranges from its humble origins in Plymouth, Massachusetts, through the presidential administrations of George and George W. Bush, and details the family's business dealings and rivalries.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy